Development of a Novel Peptide with RGD Tumor Homing Motif: Evaluation of its Anticancer Potential in Hepatocellular Carcinoma and Colon Cancer Cells - Mohamed, Reda Abdallah; Marie, Ohoud Mohammed; Badran, Dahlia Ibrahim; Hammam, Olfat Ali; Ahmed, Hend Okasha (Recent Patents on Biotechnology, 2025)
BackgroundPeptide-based therapy has emerged as a promising avenue for treating various disorders, and recent research has highlighted the potential of anti-cancer peptides (ACPs) in cancer treatment. In this context, this study aimed to design a novel peptide incorporating a tumor-homing peptide (RGD) and C-amidation to enhance its anticancer activity, particularly against liver (HepG2) and colon (HCT-116) cancer cell lines.ObjectivesThe primary objective was to design a peptide with improved anticancer properties by leveraging the tumor-homing capabilities of RGD and enhancing its activity through C-amidation. The study sought to evaluate the cytotoxicity of the designed peptide against red blood cells (RBCs) and normal Vero cells. Furthermore, the anticancer efficacy of the peptide was assessed in hepatocellular carcinoma (HepG2) and colon cancer (HCT-116) cell lines. The specific objectives included examining the apoptotic induction and morphological changes in treated cells compared to untreated cells.MethodsThe peptide was designed using the ACPred-FL bioinformatics tool, and its cytotoxicity was assessed through hemolysis assays against RBCs and normal Vero cells. Anticancer activity was evaluated against HepG2 and HCT-116 cell lines. The analysis of apoptotic induction involved measuring the relative gene expression of oncogenic marker BCL2 and apoptotic markers (BAX, BID, CAS-8). Additionally, Cytopathological examination and Western Blot analysis were employed to study morphological changes and confirm the quantification of relevant markers.ResultsThe designed peptide, consisting of twelve amino acids with a molecular mass of 1230.6233 Da and an isoelectric point of 9.81, exhibited low erythrocyte lysis and minimal toxicity to normal cells. The IC50 values demonstrated significant anticancer activity against both HepG2 (36.49±2.6 µg/mL) and HCT-116 (11.03±2.5 µg/mL) cell lines. Treated cells exhibited a significant decrease in the oncogenic marker BCL2 and an upregulation of apoptotic markers (BAX, BID, CAS-8). Western Blot analysis confirmed these results in addition to cytopathological examination that scattered apoptotic and degenerative changes.ConclusionThe designed peptide is considered a patent product that displayed remarkable anticancer activity against hepatocellular carcinoma and colon cancer cell lines, effectively modulating apoptotic and oncogenic markers. These findings highlight the potential of the peptide as a therapeutic agent for cancer treatment, emphasizing its clinical significance in combating liver and colon cancers. Nonetheless, further research and development are warranted to explore the translational potential of this peptide in clinical studies.
Keywords: colon cancer